Effect of activated charcoal alone or given after gastric lavage in reducing the absorption of diazepam, ibuprofen and citalopram - Lapatto-Reiniluoto, O (Blackwell Science Inc, 1999)
AIMS: The efficacy of activated charcoal alone, and gastric lavage followed by charcoal in reducing the absorption of diazepam, ibuprofen and citalopram was studied in healthy volunteers. METHODS: In a randomized cross-over study with three phases, nine healthy volunteers were administered single oral doses of 5 mg diazepam, 400 mg ibuprofen and 20 mg citalopram, taken simultaneously after an overnight fast. Thirty minutes later, the subjects were assigned to one of the following treatments: 200 ml water (control), 25 g activated charcoal as a suspension in 200 ml water or gastric lavage followed by 25 g charcoal in suspension given through the lavage tube. Plasma concentrations of diazepam, ibuprofen and citalopram were determined up to 10 h. RESULTS: The AUC(0,10 h) of diazepam was reduced by 27% (P < 0.05) by both charcoal alone and charcoal combined with lavage. The increase in plasma diazepam concentration from 0.5 h onwards was prevented by both interventions (P≤0.05), whereas the C(max) of diazepam was not significantly affected by either treatment. The AUC(0, 10 h) of ibuprofen was reduced by 49% (P < 0.05) after the combination treatment and by 30% (P < 0.05) after charcoal alone, but there was no significant difference between these two treatments. Both charcoal alone and the combination treatment were equally effective in preventing the increase in plasma ibuprofen from 0.5 h onwards (P < 0.01). The C(max) of ibuprofen was reduced by 45% (P < 0.05) and by 21% (P = NS), respectively. The AUC(0,10 h) of citalopram was reduced by 51% (P < 0.05) after both charcoal alone and charcoal combined with lavage, and the C(max) by 52% (P < 0.05) and 54% (P < 0.05), respectively. The increase in plasma citalopram concentration from 0.5 h onwards was reduced by about 50% (P < 0.01) by both interventions. CONCLUSIONS: Activated charcoal alone and charcoal combined with lavage showed similar efficacy in preventing the absorption of diazepam, ibuprofen and citalopram. These results suggest that gastric lavage needs not be routinely performed before administration of charcoal.